Fundamental movement skills and perceived competence, but not fitness, are the key factors associated with technical skill performance in boys who play grassroots soccer. Issue 2 (3rd April 2022) - Duncan, Michael; Eyre, Emma L. J.; Noon, Mark; Morris, Rhys; Thake, Doug; Clarke, Neil
ABSTRACT: Objective: This study examined the association between fitness, fundamental movement skills (FMS) and perceived competence on technical skills in boys engaged in grassroots soccer. Methods: Sixty boys (8-12 years of age, Mean ± SD = 10 ± 1 years) undertook assessment of FMS, perceived competence, physical fitness (15m sprint speed, standing long jump distance and seated 1kg medicine ball throw as a composite z-score) and technical skills (dribbling, passing and shooting as a composite z-score). Results: Multiple backwards linear regression was used to determine to amount of variance in technical skill explained by FMS, perceived competence and fitness. Results indicated a significant model (F 3, 58= 42.04, P = .0001, Adj R2 = .680) which explained 68% of the variance in technical skills. Perceived competence (β=.316, P =.001), Total FMS (β=.140, P =.002), and chronological age (β=.863), P =.001) significantly contributed to the model. Conclusion: This study demonstrates that better technical skills (passing, dribbling, shooting) in youth soccer are explained, alongside age, by being competent in FMS and having a more positive perception of competence. Coaches should therefore seek to encourage development of these factors during childhood for the benefit of technical skill performance.